PELATIHAN MICROGRID UNTUK MASYARAKAT INDUSTRI DAN PENDIDIKAN PADA TAMBAK UDANG VANNAMEI DI CV. RIZ SAMUDRA, JEPARA, JAWA TENGAH - Pratomo, Leonardus H; Setiawan, Slamet Riyadi, F. Budi; Wibisono, Arifin; Setiono, Felix Y; Perkasa , Gregorius D (Universitas Mataram, 2024)
The need for electrical energy supply in vannamei shrimp ponds continues to increase along with the growth of the ponds location and market demand for shrimp supply. Electrical energy supply is required to turn the aerator to get adequate oxygen intake and other needs, such as street lighting. Aerator rotation is always managed by adjusting the rotation of a three-phase induction motor. The energy supply failure can result in the growth of shrimp stunted. Kerdaireka Grant is a collaborative solution for universities and partners to overcome this problem. The purpose of this service is to train shrimp ponds industry communities and university students to understand and understand microgrid systems based on solar power plants in order to get free electricity supply. The method of this activity was carried out in two stages, first by theoretical studies of solar microgrids and the working principles of microgrids which were provided in presentations by utilizing audio-visual devices. The second stage was carried out practically related to the operation of the microgrid system and troubleshooting directly at the power house location. From this activity, the interest of the industrial and educational community is very enthusiastic, this can be seen from several independent students studying at the independent campus who are very interested and repeatedly ask for training at the location. The solar power plant microgrid is still accepting learning for anyone to study and practice directly on the vannamei shrimp ponds located in Jepara Distric.